Macroeconomic impacts of trade credit: An agent-based modeling exploration - Michel Alexandre; Gilberto Tadeu Lima (EconomiA, 2020)
This paper explores the effects of trade credit by assessing its macroeconomic impacts on several dimensions. To that end, we develop an agent-based model (ABM) with two types of firms: downstream firms, which produce a final good for consumption purposes using intermediate goods, and upstream firms, which produce and supply those intermediate goods to the downstream firms. Upstream firms can act as trade credit suppliers, by allowing delayed payment of a share of their sales to downstream firms. Our results suggest a potential trade-off between financial robustness as measured by the proportion of non-performing loans and the average output level. The intuitive reason is that greater availability of trade credit, which however does not necessarily imply proportionately greater actual use of it by downstream firms, allows more financial resources to remain in the real sector, favoring the latter's financial robustness. Yet, given that trade credit is proportionally more beneficial to smaller downstream firms, it enhances market competition. This results in a decrease in markups and thereby in profits and dividends, which contributes negatively to aggregate demand formation.
Keywords: C63; E27; G32; 330; Agent-based modeling; Macroeconomic effects; Trade credit